A unique fuzzy multivariate modeling approach for performance optimization of maintenance workshops with cognitive factors - Azadeh, A.; Ghaderi, S. F.; Pashapour, S.; Keramati, A.; Malek, M. Rezaei; Esmizadeh, M. (International journal of advanced manufacturing technology, 2017)
This paper puts forward an integrated fuzzy simulation-fuzzy data envelopment analysis (FDEA)-fuzzy cognitive map (FCM) algorithm for performance optimization of maintenance workshops by incorporating cognitive and time-dependent factors. Due to severe ambiguousness associated with the collected data, the fuzzy set theory is incorporated into the approach. Fuzzy computer simulation is employed for modeling the workshop and providing time-dependent factors. FCM is used for extracting relations between cognitive factors. FDEA is used for ranking scenarios based on inputs and outputs of FCM and the developed computer simulation. Moreover, a recent possibilistic programming approach is used to convert the fuzzy DEA model to an equivalent crisp model. The sensitivity analysis show that α = 0.1 is the best α -cut level for interpreting data. The proposed algorithm is capable of modeling and optimizing the performance of maintenance workshops in uncertain and non-linear environments. The solution quality is inspected and shown through an actual maintenance workshop. This is the first study that presents an integrated non-crisp algorithm for performance optimization of maintenance activities with cognitive and time-dependent factors.